Depozice gallium-nitridových tenkých vrstev na křemíkové substráty strukturované elektronovou litografií - Knotek, Miroslav (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2013)
Bakalářská práce se zabývá depozicí tenkých vrstev nitridu gallitého (GaN) na křemíkové substráty, které byly strukturovány elektronovou litografií. V práci jsou zkoumány možnosti použití rezistů pro selektivní růst nanostruktur za zvýšených teplot.

This bachelor's thesis deals with a fabrication of gallium nitride (GaN) thin films on silicon substrates, which were structured by electron beam lithography. In thesis, different resists for selective growth of nanostructures at elevated temperatures are examined.
Gallium-nitride thin-film deposition on substrates structured by electron beam lithography
Keywords: Nitrid gallia; elektronová litografie; depozice tenkých vrstev; selektivní růst; molekulární epitaxe; pozitivní a negativní rezisty.; Gallium nitride; electron beam lithography; deposition thin films; selective growth; molecular epitaxy; positive and negative resists.